2001
DOI: 10.1002/job.118
|View full text |Cite
|
Sign up to set email alerts
|

Do national levels of individualism and internal locus of control relate to well‐being: an ecological level international study

Abstract: SummaryData were collected from managers in 24 nations/territories on work locus of control (LOC), individualism±collectivism (I±C), and well-being (job satisfaction, absence of psychological strain, and absence of physical strain). There were signi®cant mean differences across samples on all ®ve of these measures, and consistent with our hypothesis, at the ecological or sample mean level well-being was associated with an internal locus of control. However, contrary to our hypothesis, well-being was not associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
1
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(80 citation statements)
references
References 43 publications
1
73
1
5
Order By: Relevance
“…Finally, parents also seemed to be better at acknowledging their own responsibility in their child's development. An internal locus of control is associated with greater well-being (Spector et al, 2001;Steptoe & Wardle, 2001) and less stress (Dunn, Burbine, Bowers & Tantleff-Dunn, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…Finally, parents also seemed to be better at acknowledging their own responsibility in their child's development. An internal locus of control is associated with greater well-being (Spector et al, 2001;Steptoe & Wardle, 2001) and less stress (Dunn, Burbine, Bowers & Tantleff-Dunn, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…Locus of control, defined by Rotter (1966) as a person's perception of their control over event outcomes, has been found to impact on personal wellbeing in a range of cultural contexts (see eg., Garcia et al, 2002;Kulshrestha & Sen, 2006;Spector et al, 2001). Dispositional optimism, defined by Scheier and Carver (1985) as the propensity to generally expect favourable outcomes over unfavourable ones, has also been demonstrated to co-vary with perceived well-being (see eg., Isaacowitz, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In a 23-country study, found that PD was negatively related to the frequency of outgroup disagreements; within collectivistic nations, disagreements were more frequently handled through reliance on rules rather than personal experience or training (the opposite was found for individualistic nations); and within low PD nations, ingroup disagreements were handled more frequently through reliance on subordinates whereas outgroup disagreements were more frequently handled through reliance on peers (compared with reliance on supervisors). Finally, Spector et al (2001b), using survey data from over 5,000 managers in 24 countries, found that IND was positively related to both internal locus of control and job satisfaction.…”
Section: Country Scores)mentioning
confidence: 99%
“…IND-COL moderated the relationship between marriage and life satisfaction such that it is stronger in collectivistic than individualistic countries (Diener et al, 2000). Spector et al (2002) found that IND-COL did not moderate the relationship between locus of control and well-being (using the same data from Spector et al, 2001b). Finally, in a study of 295 IJVs in the PRC, cultural distance moderated the relationship between control and performance such that when cultural distance from the host country was higher, rather than lower, there was a weaker positive relationship between control and performance for foreign, but not Chinese, parents .…”
Section: Research Challengesmentioning
confidence: 99%